Antimicrobial resistance of Escherichia coli recovered from broiler farms and slaughterhouses and impact of disinfectant use on resistance during COVID-19 pandemic - HU Yujie; PENG Zixin; XU Jin; LI Fengqin (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo understand the antimicrobial resistance of Escherichia coli recovered from breeding and slaughtering of broiler chickens, and to explore the impact of disinfectant use on resistance during COVID-19 pandemic.MethodsA total of 722 strains of Echerichia coli, isolated from broiler farms and slaughterhouses in Henan, Shandong and Liaoning provinces, were tested for resistance of 27 kinds of antimicrobial compouds belonging to 12 categories using broth dilution method, and the changes of antimicrobial resistance of strains from Shandong province before and after the outbreak of COVID-19 were analyzed.ResultsAn overall high level antimicrobial resistance was found among 722 Escherichia coli isolates, 96% of which were drug resistant strains. The resistance rate of 9 drugs in 6 categories, including AMP, was higher than 75% with the highest one of 88.1%, eight drugs got the intermediary rate of over 10%, and multiple drug resistant strains accounted for 94.7% of all resistant strains; a total of 517 drug resistance profiles were found. The strains resistant to 10 and 9 drugs ranked the top, and 118 strains were resistant to 11 kinds of antimicrobial compounds at the same time, with 2 of which were resistant to 24 drugs. Resistance of Escherichia coli isolates in Shandong province to DOX, PB and AMS/AMC increased significantly after COVID-19 pandemic.ConclusionThe overall antimicrobial resistance of Escherichia coli isolates recovered from broiler farms and slaughterhouses in China is at a very high level, and the multi-drug resistance is serious, which may be related to the long-term widespread use of related drugs in the upstream of the food chain. During the COVID-19 outbreaks, the disinfection measures in broiler breeding and slaughter processing might be related to the enhancement of the Escherichia coli antimicrobial resistance to some drugs. Continuous active surveillance from a preventive perspective should be carried out to fully assess the upside risk to antimicrobial resistance of the pathogens recovered from the food chain by the use of disinfectants.